Valuation of ecological resources : integration of ecology and socioeconomics in environmental decision making : from the Society of Environmental Toxicology and Chemistry workshop on Valuation of Ecological Resources: Integration of Ecological Risk Assessment and Socio-Economics to Support Environmental Decisions, Pensacola, Florida, USA, 4-9 October 2003 /: integration of ecology and socioeconomics in environmental decision making : from the Society of Environmental Toxicology and Chemistry workshop on Valuation of Ecological Resources: Integration of Ecological Risk Assessment and Socio-Economics to Support Environmental Decisions, Pensacola, Florida, USA, 4-9 October 2003. (©2008) - Unknown
No abstract available